Organization-public relationships practices in university setting - Mohammed, Rosli (Elsevier Ltd., 2014)
The purpose of this paper is to share the explicate and the linkages among relationship management quality indicators, of organization-public relationship were; trust, commitment, community involvement, participation and satisfaction, and types of organization-public relationship status. Data was collected by using questionnaire. It was proved that effective public relations practices makes organizations more effective and views relationship management in an even more potent role to meet corporate value enhancing objectives. In doing that the organizations need/must re-examine their OPR practices from public perceptions about how it reflect its relationships management quality and become a competitive advantage in itself.